Kritik Hukum Islam Atas Sanksi Pidana Pelaku Prostitusi dalam Peraturan Daerah - Rosadi, Aden; Nashrulloh, Nashrulloh (Universitas Islam Negeri Raden Intan Lampung, 2017)
This article examines the Regional regulations relating to prohibition of prostitution in Indonesia from the perspectives of Indonesian Law and Islamic Criminal Law. As this study reveals, a number of contradiction occurs between Regional Regulations with Criminal Code. Such contradictions can be found in a number of regional regulations prohibiting prostitution, such as : No. 5/2002 of Cirebon Regency; Regulation No. 6/2003 of Medan City; Regulation No. 2 /2004 of Palembang City, Regulation No. 13/2002 of South Sumatra Province, etc. The contradictions include the determination of the authorized officers to handle the matter, the rules in case of erroneous arrest, and the determination of sanctions. The Criminal Code sets aside sanctions for Commercial Sex Workers (CSWs) and users of CSWs. It only prohibits of facilitating the immoral acts by other parties.. In Islamic criminal Law, prostitution is considered as a crime whose perpetrators are equated with adulterers sanctioned with stoning or whip.